Identification of Histopathologic Criteria to Differentiate Autoimmune Hepatitis (AIH) from Chronic Viral Hepatitis (B, C) in Liver Biopsy Samples - Mohammadhossein Sanei; Azar Naimi; Pardis Nematolahy; Yaser Moein (مجله دانشکده پزشکی اصفهان, 2017)
Background: Chronic hepatitis is a common disease in the community. Differential diagnosis of hepatitis is very important in the treatment of this disease; as applying the wrong treatment method can lead to reinforcement and aggravate. This study aimed to determine the prevalence of histopathologic criteria for distinguishing between and for accurate differentiation of chronic viral hepatitis from autoimmune hepatitis.